2014
DOI: 10.1089/hum.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Delivery of Helper-Dependent Canine Adenovirus Corrects Neuropathology and Behavior in Mucopolysaccharidosis Type VII Mice

Abstract: Canine adenovirus type 2 vectors (CAV-2) are promising tools to treat global central nervous system (CNS) disorders because of their preferential transduction of neurons and efficient retrograde axonal transport. Here we tested the potential of a helper-dependent CAV-2 vector expressing β-glucuronidase (HD-RIGIE) in a mouse model of mucopolysaccharidosis type VII (MPS VII), a lysosomal storage disease caused by deficiency in β-glucuronidase activity. MPS VII leads to glycosaminoglycan accumulation into enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 49 publications
(58 reference statements)
4
28
0
1
Order By: Relevance
“…Additionally, while the interest of CAV-2 vectors for gene therapy increases (Ariza et al 2014;Cubizolle et al 2014), the development of scalable production processes using a suspension cell line is important to streamline the bioprocess for clinical-grade material. Here, we report the use of the new MDCK.SUS2 cell line for the production of CAV-2 in serum-free suspension cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while the interest of CAV-2 vectors for gene therapy increases (Ariza et al 2014;Cubizolle et al 2014), the development of scalable production processes using a suspension cell line is important to streamline the bioprocess for clinical-grade material. Here, we report the use of the new MDCK.SUS2 cell line for the production of CAV-2 in serum-free suspension cultures.…”
Section: Discussionmentioning
confidence: 99%
“…b-glucuronidase deficiency has also been linked to neuroinflammation. We demonstrated that as little as 10 10 physical particles of a HD CAV-2 vector expressing b-glucuronidase restores the global brain bglucuronidase activity, reduces GAG accumulation, corrects the histological hallmarks (enlarge of GAG + storage vesicles and irregular lysosome morphology) of MPS VII in the brains of MPS VII mice and dogs brains [8 , 45,46]. More strikingly, MPS VII mice display improved cognitive functions following HD CAV-2 vector injections [46].…”
Section: Cav-2 Vectors To Understand and Treat Neurodegenerative Disementioning
confidence: 99%
“…We demonstrated that as little as 10 10 physical particles of a HD CAV-2 vector expressing b-glucuronidase restores the global brain bglucuronidase activity, reduces GAG accumulation, corrects the histological hallmarks (enlarge of GAG + storage vesicles and irregular lysosome morphology) of MPS VII in the brains of MPS VII mice and dogs brains [8 , 45,46]. More strikingly, MPS VII mice display improved cognitive functions following HD CAV-2 vector injections [46]. A notable result is the comparable efficacy of HD-CAV-2 vector expressing b-glucuronidase: the dose injected into the MPS VII dogs was 50 -200-fold lower than that used for adeno-associated virus vectors in the brains of MPS I and MPS III dogs [47].…”
Section: Cav-2 Vectors To Understand and Treat Neurodegenerative Disementioning
confidence: 99%
“…Switching to canine adenovirus serotype 2 (CAdV2), rather than the commonly used human adenovirus serotype 5, has the advantage of reduced immune responses and prolonged transgene expression (Keriel, Rene, Galer, Zabner, & Kremer, 2006; Perreau et al, 2007). Using CAdV2 vectors, MPS VII mice showed stable expression, reduced pathology, and improved phenotype for at least 16 weeks after a single intracranial vector injection (Ariza et al, 2014). …”
Section: Vectors For Cns Gene Transfermentioning
confidence: 99%